Contemplation and liturgy: The experience of St. Mary Magdalene De’ Pazzi (Florence, 1566-1607) - M. O'Neill (Acta Theologica)
The article endeavours to draw some comparison between the experience of St. Mary Magdalene de’ Pazzi, the 16thcentury Italian Carmelite mystic, and the renewal of the Liturgy proposed by the Second Vatican Council, in the Constitution on the Liturgy, Sacrosanctum Concilium, 1963. This reform called for the full, active, and conscious participation of all the faithful, and it showed the unity there must be between the Liturgy of the Word and the Liturgy of the Eucharist. In the experience of the Italian mystic, the Word that was proclaimed in the Liturgy, particularly in the Eucharist, captured her whole attention, in mind and heart, when meditated upon when she had received Holy Communion. Revelation contained in the proclamation of the Word became the content of her encounter with God, leading to that moment when her encounter took her beyond words and concepts into intimate union with God.